2019
DOI: 10.3390/ijms20102416
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Immunosuppressive Microenvironment of Classic Hodgkin Lymphoma and Therapeutic Approaches to Counter It

Abstract: Classic Hodgkin lymphoma (cHL) is characterized by a few tumor cells surrounded by a protective, immunosuppressive tumor microenvironment composed of normal cells that are an active part of the disease. Hodgkin and Reed–Sternberg (HRS) cells evade the immune system through a variety of different mechanisms. They evade antitumor effector T cells and natural killer cells and promote T cell exhaustion. Using cytokines and extracellular vesicles, they recruit normal cells, induce their proliferation and “educate” … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 170 publications
1
49
0
7
Order By: Relevance
“…T cells are the main cell type in the tumor microenvironment. Without intervention, CD4 + T cells and Tregs are the main cell types, and the level of CD8 + T cells is usually very low [24]. An increase in the number of anti-tumor lymphocytes and cytokines in the tumor microenvironment can enhance the anti-tumor immune response [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells are the main cell type in the tumor microenvironment. Without intervention, CD4 + T cells and Tregs are the main cell types, and the level of CD8 + T cells is usually very low [24]. An increase in the number of anti-tumor lymphocytes and cytokines in the tumor microenvironment can enhance the anti-tumor immune response [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In the SBHFRT group, the rate of increase of CD4 + and CD8 + cells on day 7 was higher than that on day 14, and the rate of decrease of Foxp3 + cells was higher than that on day 14. The reason for this may be that SBHFRT rather than CFRT can induce higher expression levels of T helper lymphocytes and cytotoxic T lymphocytes, especially 7 days after radiation; promote the accumulation of the anti-tumor cytokine IFN-γ [26]; regulate T lymphocyte decrease, which is beneficial to reduce tumor cell immunosuppression; and recruit more DCs and cytotoxic T lymphocytes, enhancing tumor cell antigen recognition, and in turn having a stronger antitumor effect [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…Rzadszą postacią HL jest chłoniak guzkowy z przewagą limfocytów w obrazie histopatologicznym (ang. nodular lymphocyte-predominant Hodgkin lymphoma, NLPHL) [4,7,11]. W zależności od struktury, liczby i mikrośrodowiska komórek, cHL dzielimy na cztery podtypy, przedstawione w Tabeli 1.…”
Section: Omówienie • Wykrywanie I Ocena Stopnia Zaawansowania Hlunclassified
“…In patients with HL, studies have shown that: (1) the immunosuppressive nature of the TME speci ically inhibits proliferation and activity of NK cells, (2) malignant Reed-Sternberg cells and other components of the TME express ligands to inhibit NK cells, and (3) although NK cell de iciency begins at the tumor site, ultimately it progresses systematically in patients with advanced disease as the secretion of cytokines and chemokines mediates the systemic immunosuppression. Thus, strategies to reactivate NK cell function or those aimed at blocking the evasive mechanisms displayed by the TME may ultimately identify new immunotherapeutic targets [230,231]. In patients with HL, CD 123 (IL-3Rα) is frequently expressed by malignant cells and the combination of NK cells and the fully humanized anti-CD 123 monoclonal antibody (CSL362) represents a promising future therapeutic strategy [144].…”
Section: Nk Cells In Lymphomasmentioning
confidence: 99%